2017
DOI: 10.21767/1989-5216.1000228
|View full text |Cite
|
Sign up to set email alerts
|

Motorcyclists’ Mortality Pattern in Colombia from 2000 to 2013: A Longitudinal Study

Abstract: Background: Road traffic injuries and fatalities have increased in Colombia despite that 2011-2020 had been declared as the Decade of Action for Road Safety in the world. Then, this paper aims to describe the trends of motorcycle mortality patterns in Colombia from 2000-2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Given their understanding of the close link between RTCs and neurotrauma, as well as the predominant vehicle on the road being the motorcycle, participants described helmet use in the population, which was found to be lacking. This is not new where recent studies conducted in Colombia have indicated that despite laws on the mandatory use of motorcycle helmets, there have been problems surrounding enforcement and overall compliance with this legislation [37,42]. Qualitative work with motorcyclists in certain cities in Colombia has also highlighted how there is the perception that helmet use is for avoidance of penalties, rather than for safety-another issue that was evident from our findings [42].…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Given their understanding of the close link between RTCs and neurotrauma, as well as the predominant vehicle on the road being the motorcycle, participants described helmet use in the population, which was found to be lacking. This is not new where recent studies conducted in Colombia have indicated that despite laws on the mandatory use of motorcycle helmets, there have been problems surrounding enforcement and overall compliance with this legislation [37,42]. Qualitative work with motorcyclists in certain cities in Colombia has also highlighted how there is the perception that helmet use is for avoidance of penalties, rather than for safety-another issue that was evident from our findings [42].…”
Section: Discussionmentioning
confidence: 51%
“…The findings also demonstrate links between the determinants and impact of RTCs, when participants were able to identify the social and economic implications of death and disability from RTCs in the context of neurotrauma being the most common injury sustained by victims. In Colombia, as with other LMICs, one of the groups with the highest deaths and injuries from RTCs are adults under the age of 40 [20,23,37,38]. As most who are affected are men, and given the gender disparities in economic opportunities, the financial loss to families directly, and to nations, indirectly, is great, [37,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations